Uji Sifat Fisika Tanah Pada Lahan Kebun Campuran dan Sawah Pasang Surut di Desa Wajok Hilir, Kabupaten Mempawah - Alkam, Iswahyudi Yuas; Nusantara, Rossie Wiedya; Anshari, Gusti Zakaria (Soil Science Department, Faculty of Agriculture, Tanjungpura University, 2026)
Tidal land has great potential for agricultural development, but the characteristics of its soil physical properties can be affected by seawater fluctuations. This study aims to examine the physical properties of soil in two types of land use, namely mixed gardens and tidal rice fields in Wajok Hilir Village, Mempawah Regency. The parameters analyzed include field capacity water content, bulk density, porosity, and soil texture. The sampling method was carried out in full at five replication points in each land, and the analysis was carried out in the laboratory of the Faculty of Agriculture, Tanjungpura University. The results showed that the highest field capacity water content was found in tidal rice fields at 199.73%, while mixed gardens only 76.98%. The bulk density of paddy soil was lower (0.4 g/cm³) than mixed gardens (0.72 g/cm³), indicating that the paddy soil was looser. The porosity of paddy soil was also higher (78%) than mixed gardens (65.27%). Both types of land have the same soil texture, namely silt loam, which supports the ability to store water and nutrients. These findings indicate that water management and organic matter content greatly influence the physical properties of soil in supporting land productivity.